Magnificence a novel - Millet, Lydia 1968- (W.W. Norton & Company, 2013)
Susan Lindley is adrift after her husband's death. Suddenly gifted her great uncle's Pasadena mansion, she decides to restore his extensive collection of preserved animals. Meanwhile, a menagerie of uniquely damaged humans-- including a cheating husband and a chorus of eccentric elderly women-- joins her in residence. As Susan defends her inheritance from freeloading relatives and explores the mansion's many mysterious spaces, she emerges from the sudden dissolution of her family